A novel methodology for time-domain characterization of a full anechoic chamber for antennas measurements and exposure evaluation - Chakib Taybi; Mohammed Anisse Moutaouekkil; Bachir Elmagroud; Abdelhak Ziyyat (Institute of Advanced Engineering and Science, 2021)
In this paper we present a novel methodology for time-domain characterization of a full anechoic chamber using the finite integral method. This approach is considered fast, accurate and not intensive for computer resources. The validation of this approach is carried out on CST-microwave studio for a full anechoic chamber intended for antennas measurement applications and electromagnetic exposure evaluation for cellular network. Low, medium and high gain sources are used in this study. The simulations are realized on a personal computer of medium performances (i7 CPU and 16 GB of RAM). The stability and the convergence of our approach are obtained thanks to local mesh and auto-regressive linear filtering techniques. The minimization of the simulation time is based on use of the Huygens sources in the place of the antennas. The maximum error of the chamber as well as the wave depolarization into the chamber are at one with the previous work and the catalogs of the principles chambers manufacturers for the proposed tests in this paper. The Full simulations time is about 15 hours in average.